16S rRNA Sequencing and Metabolomics to Analyze Correlation Between Fecal Flora and Metabolites of Squabs and Parent Pigeons - Xiaobin Li; Shengchen Zheng; Haiying Li; Jiajia Liu; Fan Yang; Xiaoyu Zhao; Yafei Liang (Animals)
Intestinal microorganisms are essential for maintaining homeostasis, health, and development, playing a critical role in nutrient digestion, growth, and exercise performance in pigeons. In young pigeons, the gut microbiota is primarily acquired through pigeon milk, meaning the microbial composition of parent pigeons directly influences microbial colonization in squabs. However, research on the correlation between the gut microbial diversity of parent pigeons and their offspring remains scarce. This study investigates the fecal microbiota and metabolites of 10 pairs of parent pigeons and 20 squabs raised under a 2 + 2 system. Fecal samples were collected at 15 days of age, and differences in the microbiota and metabolites between the two groups were analyzed using 16S rRNA sequencing and LC-MS/MS. The results showed the following: (1) Squabs exhibited significantly lower α diversity, with a reduction in their Chao1 index and observed OTUs compared to the parent pigeons. (2) Firmicutes dominated the fecal microbiota in both groups, but parent pigeon feces showed a notably higher abundance of Proteobacteria. At the family level, 10 distinct families were identified, with 9 at the genus level and 4 at the species level. (3) A LEfSe analysis identified 16 significantly different bacterial species in the parent pigeons and 7 in the squabs. Functional gene abundance was highest in the metabolism, genetic information processing, and environmental information processing pathways. (4) An LC-MS/MS analysis in cationic mode identified 218 metabolites, with 139 upregulated and 79 downregulated in the squabs relative to the parents. These metabolites were primarily concentrated in five functional categories and enriched in 33 pathways, 2 of which showed significant differences. In conclusion, significant differences in both the α and β diversity of fecal microbiota were observed between squabs and parent pigeons, with similar bacterial species but marked differences in abundance. Metabolite analysis revealed greater richness in the parent pigeon feces. These findings suggest that future gut modulation using beneficial bacteria, such as probiotics, could potentially enhance host health based on microbial and metabolite compositions.